2020
DOI: 10.3390/nu12041025
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet in Spanish Population and Its Relationship with Early Vascular Aging according to Sex and Age: EVA Study

Abstract: The objective of this study is to analyze the influence of adherence to the Mediterranean diet (MDA) and its components on early vascular aging (EVA) in a Spanish population sample free of cardiovascular disease and to analyze the differences by sex. Methods: We recruited 501 individuals aged 35–75 without cardiovascular disease by random sampling (55.90 ± 14.24 years, 49.70% men). EVA was defined in two steps: Step 1: subjects with vascular damage in carotid arteries or peripheral artery disease were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
7
15
2
Order By: Relevance
“…We found evidence of both positive and negative features in the MED populations taking part in this study. On the favorable side, and in good agreement with earlier studies also conducted in the general adult population from SP [ 15 , 16 , 28 , 30 , 37 , 42 ], PT [ 44 , 45 ], IT [ 17 ], or GR [ 19 ], our results supported a clear preference for OO against butter, with OO displaying more than 90% of subjects within the MD recommendations, and between ≈60% and 95% consuming less than one portion of butter or cream per day. Nonetheless, the target quantity for OO (≥4 tbsp/day) was reached by ≤30% of the participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found evidence of both positive and negative features in the MED populations taking part in this study. On the favorable side, and in good agreement with earlier studies also conducted in the general adult population from SP [ 15 , 16 , 28 , 30 , 37 , 42 ], PT [ 44 , 45 ], IT [ 17 ], or GR [ 19 ], our results supported a clear preference for OO against butter, with OO displaying more than 90% of subjects within the MD recommendations, and between ≈60% and 95% consuming less than one portion of butter or cream per day. Nonetheless, the target quantity for OO (≥4 tbsp/day) was reached by ≤30% of the participants.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the MED participant countries, analogous results with scores in the midrange of the scale were previously reported in SP [ 15 , 16 , 28 , 30 , 37 , 42 , 43 ], PT [ 22 , 44 , 45 ], IT [ 17 , 18 , 46 , 47 , 48 , 49 ], GR [ 50 , 51 ], and CY [ 52 ]. Other Southern European as well as some non-European MED countries [ 23 , 27 , 53 ] have also been attributed a moderate value of MD adherence.…”
Section: Discussionsupporting
confidence: 82%
“…This diet should be rich in whole grains, vegetables, fruits, legumes, and healthy fats. The Mediterranean Diet (MD) follows this eating pattern and it has shown different benefits like reduction in ischemic cardiopathology, an improved lipid profile, lower blood pressure, insulin resistance, and less risk of cancer and strokes [ 9 , 10 , 11 ]. Dietary habits, food consumption patterns, and physical activity knowledge may help national governments make more effective and efficient health policies during a potential new period of confinement.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this leads individuals into an unhealthy lifestyle and reduces their emotional wellbeing [ 16 , 17 ]. Age and socio-economic factors are therefore a key issue in the adult population, as it has been shown that increasing age advocates a healthy state and improved quality of life, responsible use of mass media, consolidation of mental and emotional processes and improved psychological well-being [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%